Rotary Endodontics in Pediatric Dentistry: Embracing the New Alternative - Chauhan, Ananya (Int J Clin Pediatr Dent, 2019)
Pulpectomy is one of the most important procedures in maintaining the necrotic primary teeth until physiologic exfoliation. In clinical practice, time efficacy is invaluable, especially in pediatric endodontics, where unpredictability and difficulty of root canal morphology adds to a clinician's challenge. The success of a pulpectomy procedure mainly depends upon the biomechanical preparation of the root canal systems. With the advent of NiTi rotary files, adult endodontic procedures have been rendered easy, but its popularity in pedodontic practice is limited. Therefore, the purpose of this article is to review the use of NiTi rotary files for root canal instrumentation in primary teeth. HOW TO CITE THIS ARTICLE: Chauhan A, Saini S, Dua P, et al. Rotary Endodontics in Pediatric Dentistry: Embracing the New Alternative. Int J Clin Pediatr Dent 2019;12(5):460–463.